Analysis of the Influence of Price Fairness, Service Quality, and Food Quality on Customer Satisfaction with Restaurant Image as a Mediating Variable at Martinique Sky Lounge Restaurant - Hannie Andanny; Ari Mulianta Ginting (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
The food and beverage (F&B) industry in Indonesia, including the Yogyakarta region, continues to demonstrate a positive growth trajectory, particularly following the pandemic period. Martinique Sky Lounge stands as one of the prominent enterprises within this sector. Despite experiencing annual revenue growth, the establishment still encounters difficulties in reaching its Customer Satisfaction Index (CSI) objectives. This research aims to investigate the influence of price fairness, service quality, and food quality on customer satisfaction, with the restaurant’s image serving as a mediating variable at Martinique Sky Lounge. Employing a quantitative approach, data were gathered through a survey involving 418 restaurant patrons. The data analysis utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS software. The findings indicate that price fairness, service quality, and food quality significantly and positively affect customer satisfaction. Moreover, the restaurant’s image has been demonstrated to play a significant mediating role in the relationship between service quality and food quality with customer satisfaction. These results contribute to the body of knowledge in service marketing and offer strategic insights for practitioners in the F&B industry to improve customer experience and enhance competitiveness in a highly competitive market environment.